Genetic characterization and pathogenicity of two recombinant PRRSV-2 strains from lineages 1, 3, 5, and 8 emerged in China - Chunhua Wei; Chen Liu; Guangsong Chen; Yuan Yang; Jiarui Li; Huijuan Dan; Ailing Dai; Cuiqin Huang; Manlin Luo; Jiankui Liu (BMC Veterinary Research)
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) is a major economic threat to the global swine industry. Currently, NADC30-like PRRSV has undergone complex recombination with local Chinese strains, which has exacerbated the evolution of PRRSV. Recently, new recombinant PRRSV-2 strains from four lineages (lineages 1, 3, 5, and 8) have emerged in China. However, information on the pathogenicity of the novel isolate in China remains limited. To further our knowledge about the isolate, FJLIUY2017 and PRRSV2/CN/G8/2018 were selected to analyze their pathogenicity for piglets. Methods The PRRSV FJLIUY2017 and PRRSV2/CN/G8/2018 strains were isolated by porcine alveolar macrophages (PAMs) and MARC-145CD163. Complete genomic sequence analyses were conducted using the DNASTAR 7.0 software and the phylogenetic tree was constructed with MEGA 7.0. Recombination events were detected using RDP V4.10 and SIMPLOT software 3.5.1. Five PRRSV-free per group were inoculated with 2 mL (2 × 105 TCID50) of the FJLIUY-2017 and PRRSV2/CN/G8/2018. Clinical signs of disease were recorded daily after challenge. Blood samples were collected from all piglets on days 0, 4, 7, 11, and 14 dpi for analysis of viral load by IFA and PRRSV-specific antibody levels by ELISA kit. Lung gross and microscopic lesions of the inoculated piglets were examined by scoring system for lung lesion. Results Full-length genome analysis revealed that FJLIUY2017 and PRRSV2/CN/G8/2018 share 89.2% identity with each other, and in particular, they had a low degree of homology (< 92%) with PRRSV sequences available in GenBank. Phylogenetic and recombination analyses revealed that the two strains were recombinant viruses from lineages 1, 3, 5.1, and 8.7 strains. Animal studies indicated that FJLIUY-2017 resulted in the typical clinical signs of PRRSV, including persistent fever, higher viremia, severe lung lesions, and 20% mortality, whereas PRRSV2/CN/G8/2018 caused moderate clinical symptoms and no mortality during the challenge period. Hyper-immune sera against the major vaccine strains JXA1-R (lineage 8) and Ingelvac PRRS MLV (Lineage 5) failed to neutralize two strains. Conclusions FJLIUY-2017 caused persistent fever, higher viremia, 20% mortality and exhibited higher pathogenicity in piglets compared to PRRSV2/CN/G8/2018. Our results suggest that recombination between different PRRSV-2 lineages can result in the development of PRRSV variants with increased pathogenicity.